Analysis, control and circuit design of a novel chaotic system with line equilibrium - Sambas, A.; Vaidyanathan, S.; Mamat, M.; Sanjaya WS, M.; Yuningsih, S.H.; Zakaria, K. (2018)
In this paper, we describe a new 3-D chaotic system with line equilibrium. A detailed analysis of the proposed chaotic system is provided with MATLAB phase portraits, equilibrium points, symmetry, invariance, Lyapunov exponents, Kaplan-Yorke dimension, bifurcation diagram and a Poincare map. For specific values of the parameters, the proposed system displays chaotic behaviour. We apply adaptive control method for the global chaos synchronization of the new chaotic systems with unknown system parameters. In addition, a new circuit implementation of the new chaotic system is reported and examined in MultiSIM. A good qualitative agreement is shown between the simulations and the MultiSIM results.